The Effectiveness of Deep Learning Approaches in Improving Literacy and Numeracy in Geography Learning - Pradika Adi Wijayanto; Juhadi Juhadi; Apik Budi Santoso; Muhammad Guruh Bintang Wicaksana; Shinta Kusumaningjati; Fajar Wahyushi Fuedsi (Yayasan Keluarga Guru Mandiri, 2026)
This study aims to implement and test the effectiveness of a Deep Learning approach that integrates literacy and numeracy competencies into Geography learning. The study is motivated by the absence of a standardized and comprehensive Deep Learning teaching module format adaptable to various Geography topics at the secondary school level to strengthen students' literacy and numeracy skills. This research developed teaching modules, student worksheets, and an information technology–based learning media called